Higher education evaluation and accreditation in Latin America and the Caribbean - Carvalho, Alexey; Malavasi, Maria Márcia Sigrist (Universidade Estadual de Campinas, 2020)
In the Latin American and Caribbean context, there are a variety of Higher Education Institutions (HEIs) and assessment and accreditation systems. This paper analyzes some of these systems, seeking to understand how they are configured, their institutional and course evaluation instruments, their stage of maturity, their relationship with the public policies of their country, as well as aspects related to the valuation of self-assessment and the institutional context. The study consists of a bibliographic and documentary research, based on the documents, laws and official information of the evaluation and accreditation bodies of each country, as well as a field research, with professors and researchers in activity in these locations, in order to capture the perceptions about these systems in each reality. The survey had respondents from eight countries: Brazil, Chile, Colombia, Ecuador, Mexico, Peru, Uruguay and Venezuela. It was observed that although there is a great diversity and formats of assessment and accreditation systems, there are very similar processes in some of them, as well as a desire of the respondents to see advance in the systems so that there is an effective contribution to the quality improvement. The results of the analysis of the documents and the perceptions gathered in the field research showed that the evaluation and accreditation systems need to overcome the bureaucratic aspects, compliance verification and to seek formative evaluations that value the self-evaluation and the pertinence of the HEIs and courses, to nurture a quality culture and continuous improvement.